The life of Herod the Great : [large type] a novel - Hurston, Zora Neale (Amistad Large Print, an imprint of HarperCollins Publishers, 2025)
In the 1950s, as a continuation of Moses, Man of the Mountain, Zora Neale Hurston penned a historical novel about one of the most infamous figures in the Bible, Herod the Great. In Hurston's retelling, Herod is not the wicked ruler of the New Testament who is charged with the "slaughter of the innocents," but a forerunner of Christ--a beloved king who enriched Jewish culture and brought prosperity and peace to Judea. Portraying Herod within this vivid and dynamic world of antiquity, little known to modern readers, Hurston's unfinished manuscript brings this complex, compelling, and misunderstood leader fully into focus.--Back cover